2018
DOI: 10.1007/s00244-018-0540-z
|View full text |Cite
|
Sign up to set email alerts
|

Brown Hare’s (Lepus europaeus) Histone H1 Variant H1.2 as an Indicator of Anthropogenic Stress

Abstract: From the liver tissues of brown hare individuals that lived in two various habitats, i.e., the agricultural region with the predominant farms and the industrial area near a metallurgical plant, histones H1 were analyzed to compare their within and between population variability. Furthermore, because agricultural production emits mainly organic pollutants and metallurgical industry is a primarily source of inorganic contaminations, we wanted to check how the brown hare individuals are sensitive for both agents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…According to the earlier reports, the histone H1 polymorphic subtypes may serve as effective markers of breeding practice 24 and breeding selection 25 as well as the indicators of environmental quality 26 and physiological features of the organisms. 27 Based on this, the newly recognized histone H1.c’ polymorphic variants were checked for their usability to evaluation a population structure and genetic diversity of guinea fowl and pheasant individuals introduced to the new environment.…”
Section: Introductionmentioning
confidence: 99%
“…According to the earlier reports, the histone H1 polymorphic subtypes may serve as effective markers of breeding practice 24 and breeding selection 25 as well as the indicators of environmental quality 26 and physiological features of the organisms. 27 Based on this, the newly recognized histone H1.c’ polymorphic variants were checked for their usability to evaluation a population structure and genetic diversity of guinea fowl and pheasant individuals introduced to the new environment.…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis was not confirmed. Additionally, there were some genetical, physiological and toxicological studies done, but again, none of the analyzed factors was found to be responsible for such a dramatic population decline, as shown in the present study [39,78,79].…”
Section: Discussionmentioning
confidence: 48%
“…Other studies demonstrate that polymorphic H1 isoforms are useful as informative markers associated with physiological (Kowalski et al 2015) and environmental features (Kowalski 2016) of organisms, critical for their adaptation and fitness. Besides a few cases of histone H1 polymorphic subtypes presented in mammals, such as H1.4 in rabbit (Pałyga 1990) and H1.2 in brown hare (Kowalski & Markowski 2018), their occurrence is best documented in examples of birds. Whereas eight out of nine avian H1 subtypes (H1.a, H1.a', H1.b, H1.b', H1.c, H1.d, H1.z and H5) were already detected as allelic proteins (for a review see Kowalski 2018), the results of recent work (Kowalski 2019) and the data presented herein show that the remaining subtype, H1.c', is also a heterogeneous protein.…”
Section: Introductionmentioning
confidence: 99%